Employer-provided health insurance and labor supply of married women - Merve Cebi (W.E. Upjohn Institute for Employment Research, 2011)
This work presents new evidence on the effect of husbands' health insurance on wives' labor supply. Previous cross-sectional studies have estimated a significant negative effect of spousal coverage on wives' labor supply. However, these estimates potentially suffer from bias due to the simultaneity of wives' labor supply and the health insurance status of their husbands. This paper attempts to obtain consistent estimates by using several panel data methods. In particular, the likely correlation between unobserved personal characteristics of husbands and wives - such as preferences for work - and potential joint job choice decisions can be controlled by using panel data on intact marriages. The findings, using data from the National Longitudinal Survey of Youth and the Current Population Survey, suggest that the negative effect of spousal coverage on labor supply found in cross-sections results mainly from spousal sorting and selection. Once unobserved heterogeneity is controlled for, a relatively smaller estimated effect of spousal coverage on wives' labor supply remains.
Keywords: J22; J32; I18; 330; Health insurance; Labor supply; Marriage; Panel data